The Protection of Cultural Heritage and the ICC: The Gap Between Aspirations and Reality Over 25 Years - Rau, Marcin (The ICC at 25: Lessons Learnt, 2025)
This chapter explores the challenges and limitations faced by the International Criminal Court (ICC) in protecting cultural heritage over the past 25 years. While the ICC has established legal frameworks to prosecute crimes against cultural property, its effectiveness is hampered by jurisdictional constraints, political interference, and the lack of a comprehensive mandate for addressing art crimes. Cultural heritage is highlighted as a cornerstone of societal identity, with its destruction constituting an assault on humanity’s shared legacy. This chapter critically engages with Schabas’s analysis of the Al Mahdi case, questioning the ICC’s interpretation of legal definitions and the broader implications for justice. Furthermore, it highlights how the principle of military necessity is often exploited as a loophole to circumvent international law and justify the destruction of cultural property. This chapter concludes with a call for international collaboration and generational leadership to ensure the preservation of cultural heritage as a global priority.Keywords: Cultural heritage, Rome Statute, art crimes, jurisdiction, military necessity loophole, cultural genocide